2021
DOI: 10.3390/biology10080732
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing and Chromosome-Scale Assembly of Plant Genomes, Brassica rapa as a Use Case

Abstract: With the rise of long-read sequencers and long-range technologies, delivering high-quality plant genome assemblies is no longer reserved to large consortia. Not only sequencing techniques, but also computer algorithms have reached a point where the reconstruction of assemblies at the chromosome scale is now feasible at the laboratory scale. Current technologies, in particular long-range technologies, are numerous, and selecting the most promising one for the genome of interest is crucial to obtain optimal resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 49 publications
(56 reference statements)
1
14
0
Order By: Relevance
“…First, we calculated the overall quality of the sequence using Merqury and Illumina reads. We obtained an average quality value (QV) of 32.8, a lower QV than that obtained with short-reads assemblies, but consistent with QV already reported for plant genomes sequenced by ONT[24]. Indeed, using Illumina reads and the CS RefSeq v2.1 assembly, Merqury computed a QV of 44.5 (Table 1).…”
Section: Resultssupporting
confidence: 85%
“…First, we calculated the overall quality of the sequence using Merqury and Illumina reads. We obtained an average quality value (QV) of 32.8, a lower QV than that obtained with short-reads assemblies, but consistent with QV already reported for plant genomes sequenced by ONT[24]. Indeed, using Illumina reads and the CS RefSeq v2.1 assembly, Merqury computed a QV of 44.5 (Table 1).…”
Section: Resultssupporting
confidence: 85%
“…Darmor-bzh v10 (Rousseau-Gueutin et al, 2020) (Table S3). Centromeric regions were determined using the method described in Zhang et al (2018) and Istace et al (2021). Briefly, we retrieved the localization of the centromeric-specific repeat sequences using BLASTN (Altschul et al, 1990) and a cutoff of one-third of the maximal density identified on the chromosome.…”
Section: Darmor-bzh V10 Genomementioning
confidence: 99%
“…Long-read sequencing technologies revolutionized plant genomics both in terms of study frameworks and methodology [ 40 , 62 ]. Long reads enable researchers to assemble large plant genomes de novo with improved contiguity, compared to the shotgun sequencing approach [ 63 , 64 ]. However, the third-generation sequencing technologies have their own limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Assembling a genome from ONT and PacBio reads simultaneously allowed researchers to delve deep into genome structure, track rearrangements, and detect more transposable elements [ 36 , 79 , 83 ]. Other options are the use of optical maps and Hi-C scaffolding, which successfully link contigs to chromosomes The received genomes become powerful sources of genetic information [ 62 , 64 , 84 ]. Therefore, the received L. usitatissimum genome can be upgraded to a chromosome scale and used in comprehensive structure analyses.…”
Section: Discussionmentioning
confidence: 99%